Pediatric deep venous thrombosis associated with Staphylococcus aureus osteomyelitis - Liu, Linlin; Guo, Lingyun; Wang, Zhuangzhuang; Wang, Qiang; Zeng, Jinjin; Chen, Tianming; Liu, Gang (The Journal of Infection in Developing Countries, 2023)
Introduction: Our objective was to evaluate clinical features of children with deep venous thrombosis (DVT) and acute hematogenous osteomyelitis (AHO) caused by Staphylococcus aureus. Methodology: We analyzed 4 years of medical records of patients with AHO and DVT caused by Staphylococcus aureus (S. aureus) and compared clinical and biochemical characteristics of AHO with and without DVT, as well as patients whose DVT dissolved in ≥ 3 weeks. Results: DVT was found in 19/87 AHO individuals (22%). The median age was 9 years (range: 0.5-15 years). 74% (14/19) patients were boys. Methicillin-susceptible Staphylococcus aureus (MSSA) was present in 58% (11/19) cases. The femoral vein and common femoral vein were the two most damaged veins (9 cases each). Anticoagulation therapy with low molecular weight heparin was given to 18 (95%) patients. Within 3 weeks of anticoagulation, 7/13 (54%) with available data had completely resolved DVT. There was no rehospitalization due to bleeding or recurrent DVT. Patients with DVT were found to be older and had increased levels of C-reactive protein, procalcitonin, D-dimer, positive blood culture, incidence of intensive care unit admission, multifocal rate, and length of hospital stay. We did not find clinical difference between patients whose DVT dissolved within 3 weeks and those with > 3 weeks. Conclusions: Over 20% of patients with S. aureus AHO developed DVT. MSSA accounted for more than half of the cases. DVT was completely resolved in more than half of the cases after 3 weeks of anticoagulant medication, with no sequelae.